The Student Perception of public transportation mode choice: A case study of Universitas Mercubuana - Pramono, Rizki; Rifai, Andri Irfan; Handayani, Susanty (DAS Institute, 2022)
Using public transportation to support one's mobility causes one to consider their mode of transportation more carefully depending on how vital one views using public transportation. Students who depend on public transit for daily mobility are particularly concerned about rearranging their priorities by those demands. This essay aims to investigate student preferences for using public transportation. With the information gathered from the questionnaire for 100 respondents, the Spider Chart was used to assess the approach utilized in choosing public transportation based on the level of interest of Mercu Buana University students. The results of the study show that there is student interest in offering public transportation to campus. Based on the ten parameters asked, students gave relatively high responses. Safety is essential for both men and women when selecting public transportation, with average values of 9.0 and 9.3 being the highest